A Low Spin Manganese(Iv) Nitride Single Molecule Magnet - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2016)
Structural, spectroscopic and magnetic methods have been used to characterize the tris(carbene)borate compound PhB(MesIm)3MnN as a four-coordinate manganese(iv) complex with a low spin (S = 1/2) configuration. The slow relaxation of the magnetization in this complex, i.e. its single-molecule magnet (SMM) properties, is revealed under an applied dc field. Multireference quantum mechanical calculations indicate that this SMM behavior originates from an anisotropic ground doublet stabilized by spin-orbit coupling. Consistent theoretical and experiment data show that the resulting magnetization dynamics in this system is dominated by ground state quantum tunneling, while its temperature dependence is influenced by Raman relaxation. © 2016 The Royal Society of Chemistry.